ANALISIS PENGARUH IMPLEMENTASI ERP TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN - Sri Ayu Pracita; Noorlaily Soewarno; Isnalita Isnalita (Universitas Jember, 2018)
This study aims to test empirically the effect of ERP implementation on profitability and corporate value. This analysis uses independent variable that is profitability and company value, and the dependent variable is ERP implementation. The sample used in this research is a manufacturing company listed on Indonesia Stock Exchange which has implemented ERP. Data collection is done by looking at the financial statements and annual report of manufacturing companies from 2010 to 2016. Research method using multiple regression method with panel data. The results of this study prove that the implementation of ERP has a significant positive effect on profitability by using Net Profit Margin, and ERP implementation also significantly influence the value of the company by using the value of the stock market. The conclusion of this research is that companies that have implemented ERP can have better performance than before implementing ERP. Keywords: ERP Implementation, Profitability, Corporate Value